Calculation and Analysis of Spur Gear Mesh Stiffness with Considering Wear - Yang Liu; Xi Cui; Jiexin Wang (Jixie chuandong)
A numerical method is proposed to calculate the mesh stiffness of spur gear with considering wear based on the potential energy method and Archard wear equation. A precise profile equation is constructed by generating method principle. Mesh stiffness for a pair of spur gears is calculated by energy method， and the piecewise Fourier serious expansion is employed to fit the total mesh stiffness. The relationship between the normal wear volume and the pressure angle at the meshing point is calculated by adopting the Archard wear equation. And the influence of wear volume on meshing stiffness is analyzed. The numerical results revealed that the wear volume at the root and top of tooth is larger than that at other meshing points， and the volume of the wear is zero at the pitch point. With the increase of the pressure angle， the wear volume decreases first and then increases. Uneven wear of the tooth surface reduced the meshing stiffness of the gear， and the meshing stiffness decreases with the increase of the wear volume. This method provides a theoretical basis for the dynamics modeling of gear system with tooth surface wear.